2008
DOI: 10.1159/000141925
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Life Events in Adolescents with Major Depression, Borderline Personality Disorder and Matched Controls: A Pilot Study

Abstract: Background: The study assessed the prevalence of life events (LE) in adolescents with major depressive disorder (MDD, n = 19), borderline personality disorder (BPD, n = 20) and matched controls (n = 20). Methods: Assessment measures included: the Child Suicide Potential Scale, the Beck Depression Inventory, the Life Events Checklist, the Childhood Sexual Abuse Questionnaire and the Childhood Trauma Questionnaire. Results: The percentage of negative lifetime LE was significantly higher in both MDD and BPD group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
30
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 70 publications
5
30
1
3
Order By: Relevance
“…Another type of abuse strongly present in the BPD group was a history of sexual abuse, in line with the few previous studies on clinical adolescent BPD (Horesh, Ratner, Laor, & Toren, 2008;Venta et al, 2012). Our finding that sexual abuse predicted BPD in adolescent patients within multivariate analysis was rather surprising, given that Fossati and colleagues (1999) reported a meta-analytically derived, modest overall effect size (r = 0.28) of childhood sexual abuse in adult BPD.…”
Section: Bpd and Childhood Maltreatmentsupporting
confidence: 89%
“…Another type of abuse strongly present in the BPD group was a history of sexual abuse, in line with the few previous studies on clinical adolescent BPD (Horesh, Ratner, Laor, & Toren, 2008;Venta et al, 2012). Our finding that sexual abuse predicted BPD in adolescent patients within multivariate analysis was rather surprising, given that Fossati and colleagues (1999) reported a meta-analytically derived, modest overall effect size (r = 0.28) of childhood sexual abuse in adult BPD.…”
Section: Bpd and Childhood Maltreatmentsupporting
confidence: 89%
“…Finally, and perhaps most importantly, this study addresses a currently underdeveloped area in personality disorder research. Specifically, this is only the third study to explore the role of sexual trauma in adolescent BPD, and it is the first to identify sexual trauma as a feature that distinguishes between BPD and general psychiatric inpatients (not only a deBulletin of the Menninger Clinic pressed group as in Horesh et al, 2003Horesh et al, , 2008. Thus the present study builds upon the very limited research that currently addresses the role of sexual trauma in adolescent BPD and draws attention to the importance of childhood sexual abuse as a serious health concern and area of future research.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, thus far only two studies have explored the apparent link between BPD and trauma in adolescents. Namely, Horesh and colleagues (Horesh, Ratner, Laor, & Toren, 2008;Horesh, Sever, & Apter, 2003) demonstrated that childhood sexual abuse successfully discriminated between patients with BPD and depressed controls using both suicidal and nonsuicidal samples. Still, the number of studies exploring BPD in youth is extremely limited.…”
mentioning
confidence: 99%
“…Depressed adolescents report significantly more negative life events than nondepressed adolescents (Horesh et al, 2008). Various life stressors have emerged as antecedents of suicidal deaths among adolescents and young adults, with domestic conflict as the most frequent life stressor (Shields et al, 2006).…”
mentioning
confidence: 99%